Pembelajaran Takhasus Alquran: Strategi Meningkatkan Prestasi Belajar Di Smp Islam Manba’ul Ulum Mayong Kabupaten Jepara, Jawa Tengah - Thoyyib, Ahmad; Natsir, Muhammad (Educatio, 2025)
This study aims to understand the learning strategies of the Takhasus Al-Qur'an program in improving students' academic achievement at7,8 And 9 SMP Islam Manba’ul Ulum Mayong, Jepara Regency. This research employs a descriptive qualitative method with a field research approach. Data collection techniques include direct observation, in-depth interviews with relevant parties, and analysis of supporting documents. The research subjects consist of teachers responsible for the Takhasus Al-Qur'an program and students participating in the program. The findings indicate that the implemented learning strategies include the talaqqi, muroja’ah, and tahfidz methods, combined with an Islamic character-building approach. Supporting factors in the implementation of this program include the school's commitment, teacher support, and parental involvement. Meanwhile, challenges faced include limited facilities, restricted time allocation, and students' varying backgrounds in understanding religious education. Through structured strategies and intensive guidance, the Takhasus Al-Qur'an program not only enhances students' memorization skills but also fosters stronger discipline and Islamic character. The implications of this study suggest that the program's success can be strengthened through optimizing learning time, improving facilities, and reinforcing support from both the school environment and families.